2015
DOI: 10.1038/srep18195
|View full text |Cite
|
Sign up to set email alerts
|

Internal fixation treatments for intertrochanteric fracture: a systematic review and meta-analysis of randomized evidence

Abstract: The relative effects of internal fixation strategies for intertrochanteric fracture after operation remain uncertain. We conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) to address this important issue. We searched PubMed, EMBASE and CENTRAL for RCTs that compared different internal fixation implants in patients with intertrochanteric fracture at 6-month follow-up or longer. We ultimately included 43 trials enrolling 6911 patients; most trials were small in sample sizes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 63 publications
6
59
0
Order By: Relevance
“…Postoperative pain is an element that affects patients' quality of life. Screw failure, femoral shaft fracture, and other implant failure-related complications may lead to long-term pain [35]. The results of the present analysis results are consistent with the findings of the above research.…”
Section: Discussionsupporting
confidence: 92%
“…Postoperative pain is an element that affects patients' quality of life. Screw failure, femoral shaft fracture, and other implant failure-related complications may lead to long-term pain [35]. The results of the present analysis results are consistent with the findings of the above research.…”
Section: Discussionsupporting
confidence: 92%
“…Yu et al . included 29 trials reporting cutout data in their meta‐analysis . The pooling of the trials showed gama nail increased the risk of cutout compared to sliding hip screw, and no significant differences were found in PFN or PFNA comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Intertrochanteric fragility fractures are common in the elderly population and are becoming increasingly frequent with continued aging of populations worldwide (14). Intertrochanteric fractures are usually treated by osteosynthesis, which includes intramedullary and extramedullary fixation (2,15). However, elderly individuals have poor bone quality, so intertrochanteric fractures in the elderly are likely to be unstable.…”
Section: Discussionmentioning
confidence: 99%
“…The number of intertrochanteric fractures in the elderly population has been increasing worldwide because of increasing life expectancy (1). Osteosynthesis has been widely used for intertrochanteric fractures (2). However, it is not always possible for elderly patients with unstable fractures to have good outcomes after osteosynthesis (3,4).…”
Section: Introductionmentioning
confidence: 99%